Photoinitiated polymerization of methyl methacrylate by phenacyl type salts - Kasapoglu, F; Aydin, M; Arsu, N; Yagci, Y (ELSEVIER SCIENCE SA, 2003)
Phenacyl onium, salts, namely N-phenacyl-N,N-dimethylanilinium-N,N-diethyldithiocarbamate (1a), phenacyl-triphenylphosphonium-N,N-diethyldithiocarbamate (II), 1-phenacyl pyridinium-N,N-diethyldithiocarbamate (111), are shown to be efficient photoinitiators for polymerization of methyl methacrylate (MMA). Plausible mechanism of the photoinitiation involves both free radical and zwitterionic processes. Phenacyl radicals formed from the homolytic cleavage of carbon heteroatom bond initiates the free radical polymerization while Lewis bases formed from homolytic cleavage followed by electron transfer or heterolytic cleavage responsible for the zwitterionic initiation. The capability of the salts to act as initiators for the polymerization of multifunctional monomer, trimethylolpropane trimethacrylate (TMPTMA), was also demonstrated. (C) 2003 Elsevier Science B.V. All rights reserved.
Keywords: phenacyl onium salts; photoinitiated polymerization; free radical polymerization; zwitterionic polymerization; CATIONIC POLYMERIZATION; ANIONIC-POLYMERIZATION; PYRIDINIUM SALTS; CYANOACRYLATES; Chemistry